Composição físico-química e propriedades tecnológicas da farinha de folhas de mandioca - Trombini, Fernanda Rossi Magali [UNESP]; Leonel, Magali [UNESP] (EIA Energy in Agriculture, 2014)
Cassava leaves can be considered an important nutritional source when compared to other commonly consumed vegetables leaves. Cassava leaves have high levels of protein, fiber and minerals, and arestill underexplored due to the lack of information regarding the use of them as afood product, as well as, their use as an industrial raw material. The consumption of cassava leaves in fresh form is impractical due to the presence of cyanide, thereby it is required a pretreatment to be performed to reduce this component. The objective of this study was to produce and characterize the four made with cassava leaves as its chemical composition, color, indices of absorption and water solubility, and pasting properties, aiming to provide information of interest for possible application as an ingredient in the food industry. Cassava leaf flour showed low moisture content (6.6 %)and significant amounts of fiber (30.68 %), protein (23.00 %), and total carbohydrate (22.27%). Drying and milling processes allowed to obtain a flour with a low content of total cyanide (0.3 mg 100g-1 ), and the presence of vitamin C (56.6 mg 100g-1 ) and β –carotene (38 mg 100g- 1 ). The color analysis of cassava leaf flour showed low lightness with, predominantly, green and yellow pigments. The cassava leaf flour presented good solubility (14.85 %) and water absorption (6.87 g gel. g-1 ). Pasting properties showed a low peak of viscosity and a higher final viscosity with a retrogradation tendency, indicating a low capacity of this flour to form gel. The flour of cassava leaves can be a good source of nutrition when used as a food ingredient in soups and pasta. However, it is not indicated to products that require high gel formation.

As folhas de mandioca podem ser consideradas fonte nutricional importante quando comparadas as outras hortaliças habitualmente consumidas. A composição química das folhas de mandioca mostra altos teores de proteínas, fibras e minerais. As folhas de mandioca ainda são pouco exploradas devido à falta de informações quanto ao aproveitamento como produto da planta de mandioca e matéria-prima industrial. O consumo das folhas de mandioca na forma fresca é inviável devido à presença de cianeto, necessitando, com isso, ser realizado tratamento prévio para a redução desse componente. Neste trabalho objetivou-se produzir e caracterizar a farinha de folhas de mandioca quanto a composição química, cor, índices de absorção e solubilidade em água e propriedades de pasta, visando a possível aplicação como ingrediente na indústria alimentícia. A farinha de folhas apresentou baixa umidade (6,6 %) e consideráveis teores de fibras totais (30,68 %), proteína (23,00 %) e carboidratos totais (22,27 %). O processo de secagem e moagem propiciou a obtenção de uma farinha com baixo teor de cianeto total (0,3 mg.100g-1 ) e com 56,6 mg.100g-1 de vitamina C e 38 mg.100g-1 de β-caroteno. A análise de cor mostrou baixa luminosidade para a farinha de folhas de mandioca com predominância de pigmentos verdes e amarelos. A farinha de folhas mostrou bons índices de solubilidade em água (14,85 %) e absorção de água (6,87 g gel. g-1 ). A análise das propriedades de pasta evidenciou baixo pico de viscosidade, com maior viscosidade final e tendência a retrogradação, indicando baixa capacidade dessa farinha em formar gel. A farinha de folhas de mandioca pode ser uma boa fonte nutricional quando usada como ingrediente alimentício em sopas e massas alimentícias. Porém, em produtos que requerem alta formação de gel, a mesma não apresenta tal propriedade.
Phisico-chemical composition and technological properties of cassava leaf flour
Keywords: Cassava leaves; Flour; Vegetable protein; Fiber; Color; Folhas de mandioca; Farinha; Proteína vegetal; Fibras; Cor